A Terahertz Circulator Based on Magneto Photonic Crystal Slab - Biaogang Xu; Dengguo Zhang; Yong Wang; Binbin Hong; Guoxiang Shu; Wenlong He (Photonics, 2023)
In this paper, a terahertz circulator based on a magneto photonic crystal slab is envisaged. The triangular lattice photonic crystals with a line defect waveguide were constructed on an Al2O3 ceramic slab. Two cylindrical ferrites and two copper-clad plates in the junction of the Y-shaped wave-guide worked as a magneto-optical cavity resonator to approve the nonreciprocal function. In the working frequency range, 0.212–0.238 THz, the isolation of the circulator was better than 20 dB, and the insertion loss was better than 1 dB. The designed circulator based on the magneto photonic crystal slab experienced low loss and a wide bandwidth that satisfied its use in the THz application.